2018
DOI: 10.1039/c7ta09239c
|View full text |Cite
|
Sign up to set email alerts
|

Phase-pure BiFeO3 produced by reaction flash-sintering of Bi2O3 and Fe2O3

Abstract: Mixed powders of Bi2O3 and Fe2O3 are shown to yield single-phase, dense nanostructured polycrystals of BiFeO3 in reaction flash sintering experiments, carried out by applying a field of 50 V cm -1 and with the current limit set to 35 mA mm -2 . The furnace was heated at a constant rate with the reaction sintering taking place abruptly upon reaching 625 o C.Remarkably, an intermediate bismuth-rich phase of the oxide that forms just before reaching the flash temperature, transforms, and at the same time sinters,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
67
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 97 publications
(72 citation statements)
references
References 70 publications
5
67
0
Order By: Relevance
“…In summary, the Néel temperatures and also the Curie temperatures for flash sintered samples are in very good agreement with those of high quality samples reported in literature …”
Section: Resultssupporting
confidence: 89%
“…In summary, the Néel temperatures and also the Curie temperatures for flash sintered samples are in very good agreement with those of high quality samples reported in literature …”
Section: Resultssupporting
confidence: 89%
“…Low melting bismuth, and myriad phases that form below the sintering temperature makes it difficult to obtain phase pure ceramic with good electrical properties. 3 Similarly mixtures of alumina and magnesia have been shown to form single phase spinel 4 ; in situ experiments have shown that in this case, phase transformation is completed a little sooner than sintering. 2 Furthermore it has been shown that mixtures of elemental powders of bismuth oxide and iron oxide can be transformed into dense single phase polycrystals, also in a few seconds, which we call reactive flash sintering (RFS).…”
Section: Introductionmentioning
confidence: 99%
“…2 Furthermore it has been shown that mixtures of elemental powders of bismuth oxide and iron oxide can be transformed into dense single phase polycrystals, also in a few seconds, which we call reactive flash sintering (RFS). 3 Similarly mixtures of alumina and magnesia have been shown to form single phase spinel 4 ; in situ experiments have shown that in this case, phase transformation is completed a little sooner than sintering. 5 In the present work, reactive flash sintering is expanded to LLZO(Al) which is constituted from oxides of Li, La, Zr, and Al.…”
Section: Introductionmentioning
confidence: 99%
“…Recent experiments, with bismuth oxide and ferric oxide to form bismuth ferrite, and with reactions between alumina and magnesia to form spinel, have shown that phase transformations and sintering can occur together during a flash experiment. Conventional sintering usually requires stoichiometric powders, adding significant cost to manufacturing.…”
Section: Discussionmentioning
confidence: 99%
“…The discovery of flash sintering is evolving into a process for the synthesis of multiconstituent ceramics that are difficult to make by conventional methods. Powders of elemental components can be mixed and flashed in mere seconds to produce single‐phase oxides of complex compositions . The phase transformation and sintering occur concomitantly.…”
Section: Introductionmentioning
confidence: 99%